Effects of plyometric training on softer vs. harder surfaces on jump-related performance in rugby sevens players - Ojeda-Aravena, A.; Azocar-Gallardo, J.; Campos-Uribe, V.; Baez-SanMartin, E.; Aedo-Muñoz, E. A.; Herrera-Valenzuela, T. (Frontiers in Physiology, 2022)
This study aimed to compare jump-related performance after plyometric training on harder vs. softer surfaces in rugby sevens players. Fourteen players were randomly assigned to the harder surface group (H-G, n = 7) and softer surface group (S-G, n = 7). Three times per week, in the morning, the players performed plyometric training on different surfaces and strength training. Before and after the 4-week intervention period, squat jump (SJ), countermovement jump (CMJ), and CMJ with arms (CMJA) tests were performed to measure vertical jump displacement (d), rate of force development (r), and power (p). The main results indicated a significant improvement in S-G for CMJd (Delta% = +8.2%; p = 0.029; ES = 0.59) and for CMJAp (Delta% = +8.7%; p = 0.035; ES = 0.44). These improvements were significant compared to H-G for CMJAd (F1,12 = 8.50; p = 0.013; ?2p = 0.41; ES = 0.83) and CMJAp (F1,12 = 7.69; p = 0.017; ?2p = 0.39; ES = 0.79). This study reveals that performance related to the counter movement jump with arms on softer surfaces after 4-week plyometric training improved vertical jump displacement and lower body power in rugby sevens players.